Learners’ attitude towards ODL during COVID-19 crisis with special reference to Tamil Nadu Open University (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This descriptive survey intends to find out learners’ attitude towards Open and Distance Learning (ODL) during COVID-19 crisis. The population was the learners studying various programmes through ODL mode under various schools of studies in Tamil Nadu Open University, Chennai during the year 2020-2021. A sample of 1081 learners was selected by voluntary response sampling method and the data were collected through online mode. A Distance Education Attitude Scale (DEAS) during COVID-19 Crisis developed and standardized by Tzivinikou, Charitaki & Kagkara (2020) was used for assessing the level of learners’ attitude towards open and distance learning during COVID-19 crisis. The collected data were statistically analyzed with percentile analysis, mean, standard deviation, t-test, F-test, Tukey’s multiple comparison test in the SPSS v.21. The findings show that the Tamil Nadu Open University learners’ are having positive attitude towards open and distance learning during COVID-19 crisis and there is no significant difference in the attitude of learners towards open and distance learning during COVID-19 crisis in terms gender, locality, programme of study, subject of the programme and employment status.